Peranan Aparat Desa dalam Pelaksanaan Administrasi Pemerintahan Desa di Desa Karyamukti Kecamatan Mootilango Kabupaten Gorontalo - Arsjad, Muh. Fachri (Universitas Gorontalo, 2018)
The main problem in the research is the role of village officials in the implementation of village administration Village Karyamukti District Mootilango Gorontalo District. The purpose of this study to determine the role of village officials in the implementation of administrative tasks of village government. The research method used is quantitative method, and research type is descriptive. Techniques of collecting data through interviews, observation and documentation. Informants in this study were the village head, three heads of affairs, and the village secretary. The results show that: First, the role of village officials in the implementation of administrative duties in the Village Karyamukti Mootilango Gorontalo Gorontalo district is still less than the maximum. The assessment is because of the three heads of affairs, both government, development, and general recognize that its role has not been maximal in carrying out its duties and functions effectively. Secondly, the factors that influence the effort of improving the village apparatus in the implementation of administrative duties in Karyamukti village are the discipline of work, education and training, facilities and infrastructure and the level of welfare of village government apparatus.